Drying parameters of rendering mortars - Salomão, Maria Cláudia de Freitas; Bauer, Elton; Kazmierczak, Claudio de Sousa (Ambiente Construído, 2018)
The objective of this article was to study the drying behavior of rendering mortars. Cement-lime mortars with different mix proportions were evaluated to analyze the influence of mix materials on water transport. The experimental program was produced to observe the transport of liquid water and vapor water in mortars during the drying process. The liquid water transport was studied through capillary absorption and the water vapor transport by the water vapor permeability test. The drying curves used to investigate drying kinetics were obtained according to the methodology recommended by European standard EN 16322. In summary, it is possible to affirm that the aggregate, the binder and water contents determine the behavior of the mortars regarding water transport. The drying index is considered a good indicator of the easiness of both liquid and vapor water transport.